TREN PENELITIAN TERJEMAH BAHASA ARAB DI INDONESIA (SYSTEMATIC LITERATURE REVIEW) - Yunianti, Fitria Sari; Fajria, Astry (Adabiyyāt: Jurnal Bahasa dan Sastra, 2023)
According to Holmes’ Map of Translation Studies, two primary research focuses on translation studies, namely pure and applied translation studies which both emerge 16 sub-research themes. This board research scope is incomparable with the diverse themes of translation studies research, particularly in Arabic translation research in Indonesia. Until now, the research on translation studies has been dominated by descriptive translation and translation criticism. Hence, there is still various research theme that can be explored. This study aims to describe the research trends in Arabic translation research in Indonesia between 2011-2021 by applying a systematic literature review method by operating an academic search engine, “Google Scholar,” with certain Indonesian, English, and Arabic keywords.   The result shows that there are 130 articles on Arabic translation research in Indonesia with six research themes: descriptive translation, translation criticism, non-linguistic descriptive translation, theoretical translation, translation aids, and translator training.  The major theme used in research is descriptive translation, while the least used theme is translation training. By describing the chance and challenge of the importance of research in translator training, this article encourages translation studies scholars to do more research in this field.